1984
DOI: 10.1093/ajcn/39.4.598
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a rice-rich versus a potato-rich diet on glucose, lipoprotein, and cholesterol metabolism in noninsulin-dependent diabetics

Abstract: Previous reports have demonstrated that noninsulin-dependent diabetes mellitus often is associated with hypertriglyceridemia linked to hyperinsulinemia and enhanced cholesterogenesis. Studies with single meals have indicated that rice as compared to potato results in a less pronounced blood glucose and insulin response. These findings initiated the current study in which eight middle-aged patients with adult-onset, noninsulin-dependent diabetes were fed a standardized diet with potato or rice as the major carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Furthermore, cooked rice supplementation resulted in lower serum total and LDL cholesterol and increased HDL cholesterol and the HDL/total cholesterol ratio, suggesting that cooked rice may have antiatherogenic efficacy by improving the plasma lipoprotein profile. Andersén et al, 19 reported that a rice-rich diet lowered lowdensity lipoprotein triglyceride levels, compared with a potato-rich diet as the main carbohydrate source in noninsulin-dependent diabetics. In the present study, cooked rice consumption lowered LDL cholesterol compared with corn starch and sucrose consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cooked rice supplementation resulted in lower serum total and LDL cholesterol and increased HDL cholesterol and the HDL/total cholesterol ratio, suggesting that cooked rice may have antiatherogenic efficacy by improving the plasma lipoprotein profile. Andersén et al, 19 reported that a rice-rich diet lowered lowdensity lipoprotein triglyceride levels, compared with a potato-rich diet as the main carbohydrate source in noninsulin-dependent diabetics. In the present study, cooked rice consumption lowered LDL cholesterol compared with corn starch and sucrose consumption.…”
Section: Discussionmentioning
confidence: 99%
“…However, they have developed a reputation as a low-quality carbohydrate [ 9 ], with many reviews citing their GI as the cause [ 3 , 10 , 11 ]. Despite limited published epidemiologic evidence on its potential risk of T2DM until after the 2000s [ [12] , [13] , [14] , [15] , [16] ], the potato was already considered a health concern based on its GI as early as the 1980s [ 17 ]. Such early observations have led to the perception that the potato may not belong in healthy dietary patterns.…”
Section: Potatoes Are a Nutrient-dense Vegetablementioning
confidence: 99%
“…A handful of clinical trials [ 17 , [44] , [45] , [46] ] on potato intake compared potatoes with foods high in refined grains with low CFQS-4 and CFQS-5 scores [ 2 ], such as white rice, bagels, pasta, and bread. Potato intake appears to have a similar impact on glucose metabolism compared with other refined grains, with preliminary data showing supportive effects on gut health while improving diet quality [ 17 , [44] , [45] , [46] ]. A 1984 study [ 17 ] provided early evidence comparing potato intake with refined grain (as a comparison of 2 carbohydrate-rich sources).…”
Section: Clinical Trials: Comparisons Mattermentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, when assessing clinical benefits, the potential for positive dietary impact on other health parameters must also be considered. Desirable effects on serum lipids, for example, in itself could provide benefit [70]. At this point it is clear that high carbohydrate, high fiber diets that use a large percentage of foods with low glycémie effect are associated with improved blood glucose control [33,34].…”
Section: The Effect Of Differences In Glucose Tolerance Upon Glycémiementioning
confidence: 99%